2018
DOI: 10.1136/bmjopen-2017-018409
|View full text |Cite
|
Sign up to set email alerts
|

Community-based rehabilitation training after stroke: results of a pilot randomised controlled trial (ReTrain) investigating acceptability and feasibility

Abstract: ObjectivesTo assess acceptability and feasibility of trial processes and the Rehabilitation Training (ReTrain) intervention including an assessment of intervention fidelity.DesignA two-group, assessor-blinded, randomised controlled trial with parallel mixed methods process and economic evaluations.SettingCommunity settings across two sites in Devon.ParticipantsEligible participants were: 18 years old or over, with a diagnosis of stroke and with self-reported mobility issues, no contraindications to physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 42 publications
(34 reference statements)
0
42
0
Order By: Relevance
“…Two of the three studies did not detect between‐group effects on change scores or within‐group effects at post‐intervention . One pilot study reported effect sizes but not statistical significance of change over time on a device‐based measure of total daily physical activity . The only study that conducted follow‐up effects detected no between‐group effects on change scores or within‐group effects .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Two of the three studies did not detect between‐group effects on change scores or within‐group effects at post‐intervention . One pilot study reported effect sizes but not statistical significance of change over time on a device‐based measure of total daily physical activity . The only study that conducted follow‐up effects detected no between‐group effects on change scores or within‐group effects .…”
Section: Resultsmentioning
confidence: 96%
“…Fourteen studies measured changes in step count using a variety of devices . Activity counts were assessed in three studies using the ActiGraph (Actigraph Corp, Pensacola), Sensewear Armband (Body Media, San Francisco), or GENEActiv (ActivInsights, Cambridge) . These devices sample activity counts associated with the user's rate of acceleration, and established cut‐points determine time spent in varying intensities of physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regaining the capacity to get up from the floor could bring significant functional and psychological benefits to people with stroke, so further research is warranted. A pilot RCT with blinded outcomes assessment has been undertaken to evaluate the acceptability of a rehabilitation programme based on ARNI principles, including the IGO technique (http://clahrc-peninsula.nihr.ac.uk/research/retrain) as well as to check the feasibility of running a definitive RCT (Dean et al, 2018). This will allow us to further assess the safety, benefits and costs of incorporating IGO training within stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…No previous research has evaluated IGO. We therefore conducted an early phase feasibility study to explore its safety, whether it can be taught and how well it works for stroke survivors prior to deciding whether to include IGO in a pilot randomised trial of a rehabilitation programme based on ARNI techniques (Dean, Poltawski, Forster, Taylor, Spencer, James, Allison, Stevens, Norris, Shepherd, Landa, Pulsford, Hollands & Calitri, 2018).…”
Section: Introductionmentioning
confidence: 99%